1974
DOI: 10.1021/ed051p485
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between frequent testing and student performance

Abstract: The educational experiment reported here was based on the premise that frequent testing should motivate students to repetitive and intensive study habits; as a consequence they should perform better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Along the same line, Geist and Soehren (1997) and Ballard and Johnson (2004) found evidence in favor of weekly quizzes compared with no quiz indicating that weekly quizzes enhance students' performance. The finding of the present study is also consistent with studies such as Martin and Srikameswaran (1974), Graham (1999) and Kamuche (2005), who confirmed that students who received weekly quizzes outscored students who received no quiz during the course. Surprisingly enough, in contrast with the aforementioned findings, Haberyan (2003), in his study, found that there was no significant difference between the weekly quiz group and no-quiz control group students' performance in the class.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Along the same line, Geist and Soehren (1997) and Ballard and Johnson (2004) found evidence in favor of weekly quizzes compared with no quiz indicating that weekly quizzes enhance students' performance. The finding of the present study is also consistent with studies such as Martin and Srikameswaran (1974), Graham (1999) and Kamuche (2005), who confirmed that students who received weekly quizzes outscored students who received no quiz during the course. Surprisingly enough, in contrast with the aforementioned findings, Haberyan (2003), in his study, found that there was no significant difference between the weekly quiz group and no-quiz control group students' performance in the class.…”
Section: Resultssupporting
confidence: 92%
“…As frequent testing motivates students to do extra work in the class (Martin & Srikameswaran, 1974), it makes the long-term retention of the materials possible. The short nature of frequent quizzes facilitates and reinforces the learning of materials in a systematic way, because everything is being tested and then stored in small chunks systematically (Fulkerson & Martin, 1981).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research concerned with the cognitive rather than the affective benefits of mastery learning has in fact focused on testing as a key variable (see Abbott and Falstrom, 1977; Catanzano and Wilson, 1977;Dorsel, 1980, Gaynor andMillham, 1976; Guskey and Gates, 1986; Martin and Srikameswaran, 1974;Rohm et al, 1986;Sussman et al. 1980;Watson, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Students can process and prepare more deeply and meticulously for only small amounts of materials in quizzes, which stimulates practice and review and encourages reading of lecture materials (Standlee et al, 1960, Williams et al, 2006Gholami and Moghaddam, 2013). To some extent, frequent quizzes may reduce stress (Dustin, 1971) and create extrinsic motivation to obtain good grades in the course (Martin and Srikameswaran, 1974), which may clarify the positive correlation between frequent quizzes and student attendance in classes (Zarei, 2008;Kibble, 2007). As implied by McDaniel et al, (2012) and Spanjers et al, (2015) even unsupervised online quizzes are beneficial not only in traditional education environments but also in the blended learning approach.…”
Section: The Benefits Of Using Quizzes and Immediate Feedbackmentioning
confidence: 94%